Growth environment influences B16.F10 mouse melanoma cell response to gene electrotransfer - Heller, L. (Bioelectrochemistry, 2021)
We developed and characterized a 3D collagen hydrogel model for B16.F10 melanoma tumors. Cells in this 3D environment exhibited lower proliferation than cells in the conventional 2D culture environment. Interestingly, the basal expression levels of several genes varied when compared to conventionally grown cells. In each growth environment, a significant number of melanoma cells were transfected by plasmid electroporation (electrotransfer), although expression could only be ascertained on the surface of the 3D constructs. Cellular responses to plasmid entry as demonstrated by pro-inflammatory cytokine and chemokine upregulation varied based on the growth environment, as did the mRNA levels of several putative DNA-specific pattern recognition receptors (DNA sensors). Unexpectedly, when plasmid DNA was delivered while cells where attached in the 2D or 3D environments, the mRNAs of the DNA sensor p204 and the inflammatory mediator TNFα were regulated in cells receiving pulses only. However, we were unable to confirm coordinate upregulation of TNFα and p204 proteins. This study confirms that cell responses differ significantly based on their environment, and demonstrates the difficulty of extending experimental observations between cell environments.